ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EFEKTIVITAS PENYUSUNAN RENCANA PENARIKAN DANA (STUDI KASUS PADA UNIVERSITAS NEGERI SEMARANG) - Herlina, Herlina; Nurchayati, Nurchayati; Hartono, Rudi; Sukirman, Sukirman (Dinamika Akuntansi Keuangan dan Perbankan, 2022)
The purpose of this study is to analyze the effect of quality human resource, quality application, reward and punishment, organization management, and socialization and training on the effectiveness of the preparation of cash withdrawal planning. This research method uses primary data with a sample of 92 respondents. The analytical tool used is SmartPLS version 3.3.3. The results of the study show that the quality of human resources and reward and punishment have a positive effect on the effectiveness of the preparation of cash withdrawal planning. Application quality and organizational management have no effect on the effectiveness preparation of cash withdrawal planning. However, socialization and training have a negative effect on the effectiveness of the preparation of cash withdrawal planning. Keywords: cash withdrawal planning (RPD), quality human resource, quality application, reward and punishment, organization management, socialization and training